Perception of Teacher Educators'on Inclusive Early Childhood Education Curriculum in South East Nigeria - Aliyu, Aliyu Yaya; Ihisota, Josephine Chinyere; Okonkwo, Juliet Amaka (Journal of Early Childhood Development and Education, 2025)
This study examines the perception of teacher educators regarding the implementation of an inclusive early childhood education curriculum in Southeast Nigeria. Employing a descriptive survey design, a purposive sampling technique was used to select 327 teacher educators from two institutions, namely Michael Okpara University of Agriculture, Umudike (MOUAU), and Alvan Ikoku Federal University of Education, Owerri (AIFUE). Data were collected using a validated questionnaire titled "Teacher-Educators Questionnaire on Inclusive Early Childhood Education Curriculum," which achieved a reliability coefficient of 0.81. Findings reveal that teacher educators generally perceive existing training programs as effective in preparing educators for inclusive practices, but identified significant barriers, including resource shortages, societal attitudes toward disability, and insufficient training on special needs education. Cultural attitudes were also found to influence the perception and willingness of educators to embrace inclusion. The study concludes that while teacher educators hold positive attitudes and a strong commitment toward inclusive education, there is a critical need for better resources, more comprehensive training, and policy reforms to overcome existing barriers. It is recommended that government and non-governmental organizations collaborate to address these challenges by providing resources, conducting awareness campaigns, and ensuring effective policy implementation to promote inclusive education.